Innovation and creative experiences of educational mathematics in secondary schools from the pedagogy of juggling - Gutiérrez Sandoval, Pavel Roel; Cervantes Holguín, Evangelina; Gutiérrez Sandoval, Iskra Rosalía (IE Revista de Investigación Educativa de la REDIECH, 2019)
The training in juggling lasted six months, using the Rehoruli method (group 1) and Ingalese (group 2) with 47 high school adolescents and two control groups without training were maintained. Both experimental groups had better results than the control groups in the final grading of math class and in the performance of tasks involving mental rotation and identification of vertices, sides and flat faces in three-dimensional figures. In addition, the Juggling Lab implementation improved the identification and execution of observed numerical patterns.